Impact of Community Forestry Policy on Farmers in Rinjani Protected Forest Area - Nandini, Ryke; Kusumandari, Ambar; Gunawan, Totok; Sadono, Ronggo (Semarang State University, 2016)
The aim of this research is to know: (1) the economic conditions of the community forestry (HKm) farmers seen from the income and the poverty level; (2) the social conditions of the HKm farmers seen from the education level and the behavior changes; and (3) the change of social economic conditions of the HKm farmers in 2008-2015. This research is conducted from April to July in 2015 and located in four HKm groups of Rinjani protected forest area (RTK I). The data collection is conducted by the interviews with questionnaire to 102 HKm farmers using the Slovinâs formula with 10% of significant degree. This is implemented in descriptive analysis. The research result shows that: (1) the average income of the HKm farmers is Rp 1,739,677 per month/ha and 59.8% of farmers are above the poverty line; (2) the farmers are increasingly aware of education (there are only 5.9% members of farmerâs family who are uneducated) and the lack of firewood utilization (there are only 23.5% farmers who are still using the firewood); and (3) in the period of 2008 to 2015 the average income of the farmers per month increases at 52,03%; the poverty level decreases at 46.5%, and there is a behavior change in which the dependence on the forest resources in the form of firewood decreasesKey words : community forest, income, poverty, behavior change